Structural and luminescence properties of Y2‐xGeMoO8:REx (RE = Eu, Tb) phosphors. (5th July 2013) - Li, Naixu; Zhou, Jiancheng; Sun, Yueming
ABSTRACT Y2‐xGeMoO8:REx (RE = Eu, Tb) phosphors were synthesized using a facile sol–gel method. The morphology and structure of the phosphors were characterized by scanning electron microscopy (SEM), transmission electron microscopy (TEM) and X‐ray diffraction (XRD); while their luminescent properties were investigated by photoluminescence (PL) spectrometry. Our results reveal that all of these Y2‐xGeMoO8:REx (RE = Eu, Tb) phosphors adopted the tetragonal phase, belonging to Scheelite (CaWO4) structure. The obtained YGeMoO8:Eu phosphors exhibit a strong emission in the red light range which can be assigned to the 5D0 → 7F2 transition of Eu3+ when it is excited at 459 nm. Under 392 and 489 nm excitation, the YGeMoO8:Tb phosphors present predominant green emission (5D4 → 7F5) at 540 nm. The highest emission of the phosphors can be achieved by adjusting the doping concentration to be 0.25 for Eu3+ and 0.15 for Tb3+, respectively. The promising luminescence properties of these materials indicate that they can be potentially applied to white‐light‐emitting diodes. Copyright © 2013 John Wiley & Sons, Ltd.